2011
DOI: 10.1002/anie.201102001
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Highly Efficient Iron Catalyst for a [2+2+2] Cycloaddition to Form Pyridines

Abstract: Transition-metal-catalyzed[2+2+2] cycloaddition reactions that use two alkynes and a nitrile is the most straightforward and powerful strategy for the construction of multisubstituted pyridines with high atom efficiency. [1,2] The iron-catalyzed [2+2+2] cycloaddition to form pyridines remains a great challenge in this field, [3,4] although significant efforts have been made in various catalytic systems (e.g. Co,[5] Ru, [6] Rh, [7] Ni, [8] Ti, [9] Zr/Ni [10] ) in the last few decades. Guerchais and co-workers d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(57 citation statements)
references
References 80 publications
5
52
0
Order By: Relevance
“…1232 The transformation was achieved using a catalyst system consisting of iron(II) iodide and 1,3-bis-(diphenylphosphino)propane (DPPP). Zinc powder was required to activate the iron species by reduction.…”
Section: Scheme 667mentioning
confidence: 99%
“…1232 The transformation was achieved using a catalyst system consisting of iron(II) iodide and 1,3-bis-(diphenylphosphino)propane (DPPP). Zinc powder was required to activate the iron species by reduction.…”
Section: Scheme 667mentioning
confidence: 99%
“…In 2006, Holland and co-workers (18) revealed that alkyne binding to a low-valent iron metal center is particularly stronger than that of phosphine. Inspired by this report, Wan and co-workers (19) developed an iron catalyst comprising of readily available FeI 2 and dppp [1,3-bis(diphenylphosphino)propane] as the phosphine ligand in the presence of Zn dust, which served as the reducing agent (Scheme 11). Efficient synthesis of pyridines was observed only at rt starting from diynes and a slight excess of nitriles in THF an unsymmetrical diyne and acetonitrile indicated a ferracyclopentadiene intermediate that might not be involved in the overall catalytic system.…”
Section: The [2 + 2 + 2] Cycloadditionmentioning
confidence: 99%
“…In 2002, Nguyen and co-workers (38) reported the olefin cyclopropanation using μ-oxo-bis[(salen)iron(III)] complexes [salen = N,N´-bis (3,5- (16)(17)(18)(19)(20) (Scheme 20). Thus, this (salen)iron complex (16) can be used as an efficient, selective, and inexpensive metal alternative to a widely used ruthenium(II) salen complex.…”
Section: B Cyclopropanationmentioning
confidence: 99%
“…4 Shortly after our initial report, Wan and co-workers published an iron-catalyzed synthesis of pyridines from diynes and nitriles (eq 2). 5 Unfortunately, relatively high catalyst loadings were required in both systems. In addition, these systems either gave pyridines in moderate yields (former) or required ten to twenty molar equivalents of nitrile (latter).…”
Section: Introductionmentioning
confidence: 99%